Electrochemical Efficient Synthesis of Two Azo Energetic Compounds - Zhang, Jinhao; Song, Yulan; Hao, Wenjia; Peng, Rufang; Jin, Bo (Synlett, 2024)
Azo compounds with a high density, high enthalpy, and excellent detonation performance have received increasing research attention. The conventional method of chemical dehydrogenation that is used to form azo compounds involves the use of strong oxidants, resulting in environmental pollution. Electrochemical organic synthesis is considered an old method and a new technology. In this work, azofurazan tetrazole {H2AzFT; 5,5′-[diazene-1,2-diylbis(1,2,5-oxadiazole-4,3-diyl)]bis-1H-tetrazole} and azofurazan hydroxytetrazole (H2AzFTO) were synthesized by a green and efficient electrochemical dehydrogenation coupling of 5-(4-aminofurazan-3-yl)-1H-tetrazole and 5-(4-aminofurazan-3-yl)-1-hydroxytetrazole, respectively. The structures of H2AzFT and (NH4)2AzFTO were fully characterized by infrared spectroscopy, nuclear magnetic resonance, and elemental analysis, and their thermal stabilities were determined by differential thermal analysis.
Keywords: azo compounds; energetic materials; electrochemistry; green chemistry; dehydrogenation; coupling reaction